Implementation of Semendo Traditional Marriage to the Semendo Communities in Rejang Lebong: Socio Normatif Study - Agusten Agusten; Yusefri Yusefri; Rifanto Bin Ridwan; Hasep Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The research in this thesis uses a qualitative descriptive method regarding the implementation of the semendo marriage system for the semendo community in curup Rejang Lebong studied through socio-normative theory. Sociologically, the agreement on determining the amount of dowry and delivery as well as the implementation of the fulfillment of the rights and obligations of husband and wife in the Semendo traditional marriage for the Semendo community in Rejang Lebong no longer follows the customs ('urf) of their region of origin, because it is influenced by science/education,religious understanding, and association. Where as normatively the agreement on determining the amount of dowry and delivery as well as the implementation of the fulfillment of the rights and obligations of husband and wife in the semendo traditional marriage for the Semendo community in Rejang Lebong does not violate the rules of islamic family law because its application is in accordance with the theory of legal istinbath al-'urf sholihah and maslahah mursalah adj-dhoruriah